The door in the wall - De Angeli, Marguerite 1889- (New York Laurel-Leaf Books, 1977)
A crippled boy in fourteenth-century England proves his courage and earns recognition from the King.
"Reprinted by arrangement with Doubleday Books for Young Readers"--T.p. verso.
"A Newbery Medal book."
Keywords: Middle Ages -- Juvenile fiction; People with disabilities -- Juvenile fiction